BRAIN-BASED LEARNING IN ENGLISH LANGUAGE TEACHING: PRINCIPLES, IMPLEMENTATION, AND CHALLENGES - Ginting, Daniel; Tungka, Novalita Fransisca (STKIP Persada Khatulistiwa Sintang, 2025)
Brain-Based Learning (BBL) aligns teaching strategies with cognitive and neuroscientific principles to optimize learning outcomes. This study explores the application of BBL in English Language Teaching (ELT), emphasizing its effectiveness in enhancing engagement, comprehension, and retention. BBL incorporates twelve key principles: parallel processing, emotional engagement, experiential learning, pattern recognition, and real-world application. These principles support active learning by leveraging multisensory experiences, social interaction, and an enriched classroom environment. The study also examines Eric Jensen’s three-phase teaching model, which consists of preparation, active learning, and reinforcement, demonstrating how these stages align with cognitive science. While BBL presents advantages such as improved motivation and more profound understanding, challenges include the need for teacher training, resource availability, and alignment with assessment methods. The findings highlight the potential of BBL to transform ELT by creating more effective and engaging learning environments. Future research should explore innovative ways to integrate BBL with emerging educational technologies to enhance its application in diverse classroom settings.Keywords: Brain-based learning; engagement; ELT